Corporate Social Responsibility Disclosure, Good Corporate Governance, Firm Value: Evidence from Indonesia's Food And Beverage Companies - Martina Merdekawati Putri; Amrie Firmansyah; Dolly Labadia (STIE Binaniaga, 2020)
This study analyzes the relation between CSR disclosure and GCG to the firm value of Indonesia's food and beverage companies. The study is designed as quantitative research based on a multiple linear regression model. This research sample consists of 20 food and beverage companies that meet the criteria of having complete financial statements and annual report for the year 2018 and 2019 with a total of 40 observations. The result suggests that CSR disclosure has a significant effect on firm value. On the contrary, GCG does not affect firm value. These findings reflect that Indonesia's food and beverage companies should improve CSR implementation if they intend to obtain a positive response from the market. Also, the company should evaluate the implementation of GCG, not only aim to comply with the regulation, but also to enhance its quality.